Taking trade to the streets : the lost history of public efforts to shape globalization - Aaronson, Susan A. (Book collections on Project MUSE., 2001)
Examines the history of trade agreement critics, focusing particular attention on the North American Free Trade Agreement [NAFTA] between Canada, Mexico, and the United States and the Tokyo and Uruguay Rounds of trade liberalization under the General Agreement on Tariffs and Trade [GATT]. [preface].